SOME OF SEMEN PHYSICAL PROPERTIES (VOLUME AND MOTILITY) OF GERMAN SHEPHERD DOGS REARED IN IRAQ DURING DIFFERENT MONTHS OF THE YEAR. - Karem, Rafid H.; Karem, Rafid H.; Ibrahim, Najlaa S.; Zaid, Nazih W. (International Journal of Psychosocial Rehabilitation, 2020)
A total of five German shepherd dogs were selected for Breeding Soundness Examination (BSE). From the resources of the Iraqi Ministry of Interior, all of them live in uniform living conditions, and are subject to constant veterinary supervision. The collection was weekly from each dog, and 120 ejaculations were collected during all months. In this study, we studied the physical properties (volume, mass motility and individual motility) of the seminal fluid of the German Shepherd dogs (GSD) breed during the six-month period (October, November and December 2019) and (January, February and March 2020). The method of semen collection was by digital manipulation. It was recorded that volume, mass motility and individual motility show significant differences at level of (P